(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article analyzes the books and practical manuals prepared by representatives of traditional medicine in Uzbekistan, focusing on their content, scientific and practical significance, and their role in preserving and promoting the traditions of traditional medicine. Particular attention is paid to publications issued during the years of independence, the systematization of knowledge on traditional medicine, phytotherapy, medicinal plants, dietary therapy, natural treatment methods, and the promotion of a healthy lifestyle. The study also highlights the importance of these books and manuals in improving public health, preserving the national medical heritage, and supporting scientific research in the field of traditional medicine.